Hubungan antara Kejadian Abortus Spontan dengan Paritas dan Usia Ibu Hamil di RSUD Dr Moewardi - Badri, Dwi Septiadi; Melinawati, Eriana; Budiani, Dyah Ratna (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Abortion is one of the health problems that causing high morbidity and mortality. there are various factors suspected to be associated with the cause of abortion including the factor of age and parity. A very young or a very old maternal age can increase the risk of abortion. So does the parity, the more parity of the mothers, the higher the risk of abortion. The purpose of this study was to determine the incidence of spontaneous abortion associated with maternal age and parity status during pregnancy. Methods: This study was an observational analytic study using cross-sectional. A total of 40 study subjects were selected by purposive random sampling was the pregnant women who become inpatients at the Department of Obstetrics and Gynecology at Dr. Moewardi State Hospital Surakarta who met the inclusion criteria . Data were collected by direct interview to the patient . The data were analyzed using logistic regression analysis test. Results: Based on the research status of pregnant women with parity â¥ 4 are 8.53 times likely to experience spontaneous abortion ( p = 0.000 , OR = 8.53 ). While pregnant women with age of < 20 years and > 35 years are 14.77 times likely to experience spontaneous abortion ( p = 0.000 , OR = 14.77 ). Conclusions: There is a significant relationship between the incidence of spontaneous abortion with parity and maternal age. Pregnant women with parity status â¥ 4 are 8.53 times likely to experience a spontaneous abortion while pregnant women with age < 20 years and > 35 years are 14.77 times likely to experience spontaneous abortion. Keywords: spontaneous abortion , parity , age Â